The manufacturing of markets : legal, political and economic dynamics - Brousseau, Eric; Glachant, Jean-Michel (Cambridge University Press, 2014)
"Different types of markets exist throughout the world but how are they created? In this book, an interdisciplinary team of authors provide an evolutionary vision of how markets are designed and shaped. Drawing on a series of case studies, they show that markets are far from perfect and natural mechanisms, and propose a new view of markets as social construct, explaining how combinations of economic, political and legal constraints influence the formation and performance of markets. Historical trajectories and interdependencies among institutional dimensions make it difficult to build costless, non-biased co-ordination mechanisms, and there are limitations to public and private attempts to improve the design of markets. The authors show that incomplete and imperfect modes of governance must be improved upon and combined in order for markets to work more efficiently. This timely book will interest practitioners and academics with backgrounds in economics, law, political science and public policy"--